Komitmen Terhadap Keselamatan Aktiviti Luar Dan Berisiko dalam Pendidikan (Sains Humanika, 2018)
Safety is an important element in carrying out all outdoor and risky activities. Certainly this activity is vulnerable to security issues whether before, during or after an activity is implemented. Various important aspects need to be taken into account when conducting outdoor and risky activities to ensure an accident that can be avoided and safe from incidents which may cause direct or indirect injury. The objective of this study is to look at the safety commitment among administrators and implementers in terms of level of knowledge, competence and safety practices of outdoor and risk activities. This study uses questionnaires and open-ended questions to administrators comprising management and implementing groups randomly. The findings show that the percentage of knowledge is very high, 93.8% is directed to not accepting specific safety-related training is 53.1% and uncertain to receive 37.5% specific safety-related training. The existence of the function of the Occupational Safety and Health Management system also noted that 71.0% of the respondents did not and were unsure, but only 6.1% of the respondents recorded uncertain how to deal with the risks during the activity. Respondent's competence to qualified and qualified assignments is a high percentage. Based on commitment and safety practices, the high percentages of respondents provide positive feedback on safety commitments and the need for safe situations during their activities in accordance with Safety Theory Dan Petersen (1982). This scenario demonstrates an effort towards strengthening the existing standard operating procedures (SOP) of outsourced and risky activities plus a risk management element is essential.
Keywords: Safety; outsourcing and risk; standard operating procedures; risk management